Yield and quality of flavor extract from two varieties of ginger (Zingiber Offficinale Roscoe) - Sy, Ana Y.; Del Valle, Mercedita (1979.)
Flavor extracts were prepared from newly harvested and stored (5 weeks) samples of Hawaiian and native varieties of ginger. The samples were first vacuum dried at 170°F and 25 mm Hg for 5 hours and then extracted with 95% ethyl alcohol for 14 hours. Most of the solvent was removed by distillation. This crude extract was evaluated for quality by determination of its volatile and fixed oil contents and sensory evaluation of beverages prepared from it. The fresh samples of native ginger gave the highest yield of crude flavor extract (48.02 gms/100 gms dried sample), the highest contents of volatile oil (1.88 gms/100 gms dried sample) and fixed oil (46.14 gms/100 gms dried sample). Storage, however, resulted in greatly decreased yields. In the Hawaiian variety, the stored samples gave slightly higher yields than the fresh samples but both were lower than that of fresh native ginger. Beverages prepared from the extracts were acceptable but rated lower than that prepared from fresh ginger.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Ginger